(untitled) (Tạp chí Nghiên cứu Khoa học Công đoàn, 2024)
The president of the grassroots trade union plays an important role in all activities of the grassroots trade union organization. The President of the Communist Party of Vietnam is the base, the head, the representative "leader" to fight and protect the legal and legitimate rights and interests of union members and workers... To organize grassroots trade unions development, improving the quality of the Trade Union Executive Committee, whose head is the owner of the trade union facility, is an important factor determining the quality of operations of the trade union organization of the trade union organization. The article focuses on analyzing the quality of grassroots crowns and some proposals to improve the quality of grassroots crowns to meet task requirements in the current situation.